2005
DOI: 10.1071/bt04162
|View full text |Cite
|
Sign up to set email alerts
|

Above- and below-ground biomass, and allometry, of four common northern Australian mangroves

Abstract: Mangrove forests are an integral part of tropical coastal ecosystems, particularly in northern Australia. In the Northern Territory, studies have determined the extent and species diversity of these associations but little is known of biomass or productivity. We sampled the above- and below-ground biomass of the four most abundant species, Avicennia marina, Bruguiera exaristata, Ceriops australis and Rhizophora stylosa, developed allometric relationships and examined partitioning. Unlike many other studies, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 17 publications
2
84
1
2
Order By: Relevance
“…This was possibly related to the age of the forest, with younger mangroves located at the expanding seaward edge. Other studies found above-ground biomass measures such as trunk circumference are good predictors for below-ground biomass in A. marina (r 2 > 0.8; Comley and McGuinness, 2005;Patil et al, 2014). The poor relationship between above and below-ground biomass and C stocks in our study may be associated with a shift in biomass partitioning due to environmental conditions (McKee, 1995;Pezeshki et al, 1997;Naidoo, 2009;Alongi, 2011;Castañeda-Moya et al, 2013).…”
Section: Below-ground Biomass and Allometry Of Temperate A Marina Focontrasting
confidence: 45%
See 2 more Smart Citations
“…This was possibly related to the age of the forest, with younger mangroves located at the expanding seaward edge. Other studies found above-ground biomass measures such as trunk circumference are good predictors for below-ground biomass in A. marina (r 2 > 0.8; Comley and McGuinness, 2005;Patil et al, 2014). The poor relationship between above and below-ground biomass and C stocks in our study may be associated with a shift in biomass partitioning due to environmental conditions (McKee, 1995;Pezeshki et al, 1997;Naidoo, 2009;Alongi, 2011;Castañeda-Moya et al, 2013).…”
Section: Below-ground Biomass and Allometry Of Temperate A Marina Focontrasting
confidence: 45%
“…australasica. Existing data suggests that belowground biomass exceeds above-ground biomass stocks in some locations (Briggs, 1977;Mackey, 1993;Tam et al, 1995;Comley and McGuinness, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An contrary observation (i.e. above:below ground biomass ratio of 2.0), has been reported by Hoque et al (2010) from Okinawa island, Japan, where the tidal amplitude is 1.5~2.0 m. Comley and McGuinness (2005) report above:below ground biomass ratio of 0.75~2.0 for four mangrove species in Darwin Harbour, Australia, under macro-tidal conditions where the amplitude ranges up to 8 m. In upland forests below ground fraction become less compared with above ground portion and the ratio ranges between 3.9 and 4.5 (Cairns et al, 1977). The two mangrove species subjected to present study that occupy an intertidal habitat with an average tidal range which does not exceed 50 cm (relatively low inundation depth, duration and frequency) results in plants with a above:below ground biomass/TOC that resembles plants living under terrestrial conditions, (i.e.…”
Section: Accuracy Of Organic Carbon Estimation Using the Allometric Rmentioning
confidence: 73%
“…For example, mangroves play an important role in global carbon cycling by acting as a sink of CO 2 (Ong 1993) and also as a significant source of dissolved organic matter (DOM) to the world oceans (Dittmar et al 2006). While both aboveground and belowground productivity in mangrove forests contribute to the high organic matter content in mangrove soils (Comley and McGuinness 2005), litterfall plays a crucial role in the nutrient cycling of mangrove forests (Odum and Heald 1975;Twilley et al 1986). Indeed, litterfall, which consists mainly of leaves, represents about one third of primary production in mangrove forests (Robertson et al 1992).…”
mentioning
confidence: 99%